3(v-4)=-3v+6

Simple and best practice solution for 3(v-4)=-3v+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(v-4)=-3v+6 equation:



3(v-4)=-3v+6
We move all terms to the left:
3(v-4)-(-3v+6)=0
We multiply parentheses
3v-(-3v+6)-12=0
We get rid of parentheses
3v+3v-6-12=0
We add all the numbers together, and all the variables
6v-18=0
We move all terms containing v to the left, all other terms to the right
6v=18
v=18/6
v=3

See similar equations:

| -4v-8=-7(v+2) | | z÷12=9z÷12=9 | | -2(w+90)=-7w+22 | | 3c-4(c-1)=-c+1 | | 3c-4(c-1)=-c+4 | | n=-3.2 | | 6i-3i=-3 | | 2x-30=-4x | | 2x–2=-8 | | -2x=-8. | | x+8=10. | | 4x+1=5. | | -2x+6=-4x+18 | | 72=5x-93 | | 4a+23-11a-17=23 | | 7c-9=6c+9 | | 5(2x-1)=3+2(3x+14) | | -13j−-9j+18j+-5j=-9 | | 4x-18=2x-20 | | 8x+8/4=64 | | 5x/4-3=-23 | | 12x+14=11x+18 | | 0.6x+4.8=9 | | 5(x+5)+3=48 | | 12x+14=11x=18 | | -7-2x=5x | | 3t+6=2t+6 | | (25x−2548)(−5)=x6−14(x+6) | | 3c+9=39 | | 3n+4=7-2n | | 9x^2=-91 | | 5=4(n+3)/2 |

Equations solver categories